What is Media Archaeology? - Parikka, Jussi (Cambridge Polity, 2012)
This cutting-edge text offers an introduction to the emerging field of media archaeology and analyses the innovative theoretical and artistic methodology used to excavate current media through its past. Written with a steampunk attitude, What is Media Archaeology? examines the theoretical challenges of studying digital culture and memory and opens up the sedimented layers of contemporary media culture. The author contextualizes media archaeology in relation to other key media studies debates including software studies, German media theory, imaginary media research, new materialism and digital humanities.